THE ORIGIN OF PAKHT?N/PUSHT?N AND THEIR ARRIVAL IN THE PESH?WAR VALLEY - Shaista Gohar; Lubna Iqbal; Tasneem Sarwat (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
ThePusht?ns/ Pakht?nsare a major ethnic group on the P?kist?n-Afgh?nist?n border. ThePusht?ns are highly concerned with origin, descent and genealogies. There are multiple claims or theories about the origin of thePusht?ns. This paper is related to the origin of Pusht?nsand their arrival in the Pesh?war valley, old name isGandh?ra. The paper also highlights the history of Y?sufzai branch and their arrival in the Pesh?war valley whose original occupation was in K?bul valley.